Competitiveness for Malaysian container hauliers operating at Bukit Kayu Hitam - Sadao border crossing (Malaysia - Thailand) in facing ASEAN economic community (AEC) / Muhamad Aziyan Hussim - Hussim, Muhamad Aziyan (2018)
This research examines the current scenario of cross border haulage operation at Bukit Kayu Hitam-Sadao border (Malaysia & Thailand) and the impact on competitiveness due to liberalisation & ASEAN Economic Community (AEC) towards haulage service providers operating at Bukit Kayu Hitam-Sadao border. The research is primarily a qualitative research with the objective to gain an understanding of underlying reasons and opinions from the stakeholders of Bukit Kayu Hitam-Sasao border point and eventually dive deeper into the problems.